Evaluating the Swedana Method for Purifying Shankha : A Scientific Approach (International Journal of Ayurveda and Pharma Research, 2024)
Shodhana is the process of conversion of poisonous drugs into non-poisonous form, thereby making them suitable for internal administration to obtain the desired therapeutic benefits. Shankha is one of the rich sources of calcium of animal origin i.e., from the shell of marine creature called Turbinella pyrum, Xanthus pyrum which are generally found in the shallow ocean coast along with the several weeds and other minerals which makes it unsuitable for direct internal administration. Hence, the intermediate process i.e., Shodhana is required. There are different methods of Shodhana like Swedana (boiling), Kshalana (washing), Bharjana (frying), Nirvapana (quenching in liquid media). This paper explores the one of the methods of Shankha Shodhana which is Swedana (boiling) of Ashuddha Shankha in lemon juice for 12 hours and different physical changes that occurred in Shankha after Shodhana viz. change in the weight, colour, hardness, texture of Shankha.